"Daddies, " "Cougars, " and Their Partners Past Midlife: Gender Attitudes and Relationship and Sexual Well-Being among Older Adults in Age-Heterogenous Partnerships. (August 2019) - Silva, Tony
Discussion of "daddies" has exploded in popular discourse, yet there is little sociological research on age-heterogenous partnerships. This paper uses data from the 2013 Midlife in the United States survey and the 2015–2016 National Social Life, Health, and Aging Project to examine age-heterogenous partnerships at older ages (63 was the approximate average age of each sample). On most measures of life satisfaction and relationship well-being, individuals in age-heterogenous partnerships—regardless of age or gender—were not very different from their counterparts in age-homogenous relationships. Some differences did emerge, however, especially related to sexual well-being. Women partnered to older men had less sex and more issues related to sexual satisfaction than their counterparts in age-homogenous relationships. Latent class analyses suggest that these differences were driven by around 40 percent of younger women partnered to older men, a minority of whom were deeply dissatisfied. This research helps address the underrepresentation of sexuality research at older ages and the sociological research gap about age-heterogenous partnerships.